Efektifitas Pelayanan Adminduk Yang Unggul Melalui Inovasi Program Kalimasada Di Kantor Kelurahan Tanah Kali Kedinding Kecamatan Kenjeran Kota Surabaya - Bahij Berliana Kusuma Dewi; Bambang Kusbandrijo (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The Kalimasada (Civil Administration Aware Community Environment) program is an inovation from the Surabaya City Population and Civil Registration Service which aims to improve Population Administration services for Surabaya City residents. Optimization of the Kalimasada program will be achieved if the administrative service itself can be carried out with superior service. Based on this background, this research aims to analyze the implementation of superior services from the Kalimasada program at the Tanah Kali Kedinding Village Office. The basic qualitative research method became the procedure for implementing this research, where the author then obtained data through interviews and observation results during the research period at the Kali Kedinding Land Office. The research results show that there are still two principles of excellent service that cannot be fulfilled in the implementation of the Kalimasada program at the Tanah Kali Kedinding Village Office. Thus, it can be concluded that the implementation of the Kalimasada program in Tanah Kali Kedinding is less effective, this may be due to the lack of clarity regarding the two principles of superior service.